2006
DOI: 10.1111/j.1469-8137.2006.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Conifers in cold environments synchronize maximum growth rate of tree‐ring formation with day length

Abstract: Summary• Intra-annual radial growth rates and durations in trees are reported to differ greatly in relation to species, site and environmental conditions. However, very similar dynamics of cambial activity and wood formation are observed in temperate and boreal zones.• Here, we compared weekly xylem cell production and variation in stem circumference in the main northern hemisphere conifer species (genera Picea , Pinus , Abies and Larix ) from 1996 to 2003. Dynamics of radial growth were modeled with a Gompert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
298
5
19

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 388 publications
(364 citation statements)
references
References 49 publications
25
298
5
19
Order By: Relevance
“…Soil drought, for instance, has been suggested to hasten the cessation of cambial activity (Dünisch and Bauch 1994;Gričar and Čufar 2008), though this result is not systematically observed (Gruber et al 2010). Day length, which likely modulates the rate of cambial division (Rossi et al 2006;Cuny et al 2012), may also act as a cue for the cessation of cambial activity, but this hypothesis remains to be tested. Finally, the ending of xylem differentiation, which marks the end of annual wood formation, occurs at similar temperatures to the prevailing temperatures during the onset of cambium cell division .…”
Section: The Phenology Of Wood Formationmentioning
confidence: 86%
“…Soil drought, for instance, has been suggested to hasten the cessation of cambial activity (Dünisch and Bauch 1994;Gričar and Čufar 2008), though this result is not systematically observed (Gruber et al 2010). Day length, which likely modulates the rate of cambial division (Rossi et al 2006;Cuny et al 2012), may also act as a cue for the cessation of cambial activity, but this hypothesis remains to be tested. Finally, the ending of xylem differentiation, which marks the end of annual wood formation, occurs at similar temperatures to the prevailing temperatures during the onset of cambium cell division .…”
Section: The Phenology Of Wood Formationmentioning
confidence: 86%
“…Cambium is a sink of carbohydrates and cambial activity requires a continuous supply of energy, extracted from the storage tissues or produced by photosynthesis (Oribe et al, 2003). The conclusion of shoot and needle lengthening occurred in July, when cambium activity slowed down (Rossi et al, 2006c). Newly produced carbon obtained from photosynthesis could be available for the deposition of cellulose microfibrils and lignin in order to provide the developing latewood cells with thick secondary walls.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant differences between species and tree parts, only temperature appeared to be an important factor affecting cell features in earlywood. Cambium activity culminates during June and July (Rossi et al, 2006c), but temperatures can still be cold, even below 0 • C (data not shown). Low temperatures are known to affect cell division, but this study demonstrated their important influence on the processes of cell maturation, so affecting the size of cells and walls.…”
Section: Climate and Cell Featuresmentioning
confidence: 99%